Women in Modern Medicine in India: Progression, Contribution, Challenges and Empowerment - Sharad Khattar (Australasian Accounting, Business and Finance Journal, 2019)
Womens’ representation in most of the professions in India was been dismally low before the country gained independence. This can be attributed to the customs and traditions which have been in vogue through the centuries. Women’s accepted role within the confines of the home and seclusion from males other than the family members were two reasons which contributed to women not being part of many professions. Medicine as a profession reflected this and thus the representation of women in medicine was insignificant in the 19th and the first half of the 20th centuries. However certain measures during the period began the process of entry of women into the profession. Opening of medical colleges and schools was an important step, although women were allowed to join in meagre numbers. Later, medical colleges only for women opened, which forced other medical colleges to admit women. This was because of the setting aside of special funds by the government for this cause and the role of women missionaries who believed it a moral duty to induct women into the medical profession in order to better serve women patients. These factors were helpful for women trying to get a foothold in the profession. The pioneering efforts of a few women doctors added impetus to this activity. It can be said with pride that there may now be more women than men enrolled in medical colleges. There are still challenges such as the unequal representation of women in all disciplines, but to change this will require a change in the mind set of Indian society rather than the enacting of any law . Empowerment of women is a widely researched topic, and this study differs country wise and profession wise from other studies. It can be presumed that the medical profession, because of its inherent characteristics, is looked upon as a noble profession and thus it might be expected to lead other professions in empowerment. The present paper traces the medical profession through the last two centuries in relation to women and the challenges faced by them. It highlights the contributions of some prominent personalities and discusses how empowered the women doctors feel who are residing in the Delhi National Capital Region (NCR). The result on empowerment reveals positivity in many aspects, but certain areas still need to improve. Further measures by the government and changes in societal patterns would be beneficial.
Keywords: Women; Medical practice; Empowerment; Contribution; India; Gender; History; Medicine.